Clinical Predictors of Liver Fibrosis Presence and Progression in Human Immunodeficiency Virus–Associated Nonalcoholic Fatty Liver Disease. (9th April 2020) - Fourman, Lindsay T; Stanley, Takara L; Zheng, Isabel; Pan, Chelsea S; Feldpausch, Meghan N; Purdy, Julia; Aepfelbacher, Julia; Buckless, Colleen; Tsao, Andrew; Corey, Kathleen E; Chung, Raymond T; Torriani, Martin; et al.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) affects more than one-third of people living with human immunodeficiency virus (HIV). Nonetheless, its natural history is poorly understood, including which patients are most likely to have a progressive disease course. Methods: We leveraged a randomized trial of the growth hormone–releasing hormone analogue tesamorelin to treat NAFLD in HIV. Sixty-one participants with HIV-associated NAFLD were randomized to tesamorelin or placebo for 12 months with serial biopsies. Results: In all participants with baseline biopsies (n = 58), 43% had hepatic fibrosis. Individuals with fibrosis had higher NAFLD Activity Score (NAS) (mean ± standard deviation [SD], 3.6 ± 2.0 vs 2.0 ± 0.8; P < .0001) and visceral fat content (mean ± SD, 284 ± 91 cm 2 vs 212 ± 95 cm 2 ; P = .005), but no difference in hepatic fat or body mass index. Among placebo-treated participants with paired biopsies (n = 24), 38% had hepatic fibrosis progression over 12 months. For each 25 cm 2 higher visceral fat at baseline, odds of fibrosis progression increased by 37% (odds ratio, 1.37 [95% confidence interval, 1.03–2.07]). There was no difference in baseline NAS between fibrosis progressors and nonprogressors, though NAS rose over time in the progressor group (mean ± SD, 1.1 ± 0.8 vs −0.5 ± 0.6; P < .0001). Conclusions: In this longitudinal study of HIV-associated NAFLD, high rates of hepatic fibrosis and progression were observed. Visceral adiposity was identified as a novel predictor of worsening fibrosis. In contrast, baseline histologic characteristics did not relate to fibrosis progression. Abstract : In this longitudinal study of HIV-associated nonalcoholic fatty liver disease, we observed high rates of hepatic fibrosis presence and progression and identified visceral adiposity as a novel predictor of fibrosis progression.